Penerapan Program Edukasi dalam Kontrol Glikemik Pasien DM Tipe 2: Systematic Review - Firda Yusniar; Shrimarti Rukmini Devy; Ika Yuni Widyawati; Abd. Rivai Dunggio (FORIKES, 2022)
Worldwide incidence of Type 2 Diabetes Mellitus (T2DM) has increased, almost 9% of the global population was estimated to suffered T2DM in 2035. The aim of this study was to evaluated impact of education programs on glycemic control in T2DM Patients. Scopus, PubMed, ProQuest and ScienceDirect were databases used to search for the keywords “Diabetes Education Programs OR Diabetes Self-Management Education” AND “Glycemic Control” AND “Type 2 DM OR Diabetes Mellitus Type 2” then obtained a number of 456 articles. Eligibility criteria assessed by PICOT framework. Fifteen studies selected with inclusion criteria: T2DM patients were has no severe symptoms, aged 18-65 years. Then obtain total of 2762 patients in this study. Interventions were given during period ranges from 3 till 24 months, each session reached 30 to 80 minutes. Averages studies showed educational programs had positive impact on self-monitoring of blood glucose and HbA1c levels. Educational programs provided conventionally by therapists, based on SMS, e-health applications and web access combined with standard care. Education helps in glycemic controlled among T2DM patients, it could be effective to applied as support program to improved diabetes self-management.Keywords: education program; diabetes self-management education; glycemic control ABSTRAK Insiden Diabetes Mellitus Tipe 2 (DMT) di seluruh dunia telah meningkat, hampir 9% dari populasi global diperkirakan menderita DMT2 pada tahun 2035. Tujuan dari penelitian ini adalah untuk mengevaluasi pelaksanaan program edukasi terhadap kontrol glikemik Pasien DMT2. Scopus, PubMed, ProQuest dan ScienceDirect merupakan database yang digunakan untuk mencari kata kunci “Diabetes Education Programs OR Diabetes Self-Management Education” AND “Glycemic Control” AND “Type 2 DM OR Diabetes Mellitus Type 2” kemudian diperoleh sejumlah 456 artikel. Kriteria kelayakan yang dinilai dengan kerangka PICOT. Lima belas studi dipilih sesuai kriteria inklusi: pasien DMT2 yang tidak memiliki gejala berat, berusia 18-65 tahun. Sebanyak 2762 responden termasuk dalam studi ini. Intervensi diberikan selama rentang waktu 3 hingga 24 bulan, setiap sesi mencapai 30 hingga 80 menit. Studi rata-rata menunjukkan program edukasi berdampak positif pada pemantauan mandiri gula darah dan kadar HbA1c. Program edukasi yang diberikan yakni secara konvensional oleh terapis, dengan media SMS, aplikasi seluler dan akses web yang dikombinasikan dengan perawatan standar. Edukasi membantu dalam kontrol glikemik pasien DMT2, serta efektif sebagai program pendukung dalam meningkatkan manajemen diri diabetes.Kata kunci: program edukasi; diabetes self-management education; kontrol glikemik